Tear-resistant, high-wear-resistant and high-flame-retardant elastomer material for artificial leather and preparation method thereof
By adding montmorillonite and phosphate flame retardant to SEBS artificial leather materials, and peeling the montmorillonite into two-dimensional nanosheets by using a dispersing mattress and oven heating method, the problem of insufficient flame retardant performance, tear resistance and wear resistance of SEBS materials is solved, and efficient enhancement and performance improvement of the material is achieved.
Patent Information
- Application Number
- CN202411721315.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-28
AI Technical Summary
The existing SEBS artificial leather materials cannot meet the needs of high flame retardant properties, and their tear resistance and wear resistance also need to be further improved to extend their service life.
By adding 1-5 parts of montmorillonite, 1-20 parts of phosphate flame retardant, 0.1-1.0 parts of crosslinking agent, 0.2-1.0 parts of accelerator, 1.0-5.0 parts of foaming agent and 0.2-1.0 parts of antioxidant to the SEBS material, the montmorillonite is peeled into two-dimensional nanosheets by combining a dispersion mattress and an oven heating method, and the mechanical properties of the material are improved through intensive refining and micro foaming processes.
It significantly improves the tear resistance, wear resistance and flame retardancy of SEBS materials, meets the needs of high-end artificial leather, and is simple in process and low in cost, making it suitable for large-scale industrial production.
Smart Images

Figure BDA0005158102690000101 
Figure BDA0005158102690000102 
Figure BDA0005158102690000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer composite materials, and in particular to a thermoplastic elastomer material for artificial leather reinforced by two-dimensional montmorillonite nanosheets and a preparation method thereof. Background Art
[0002] Natural leather is easy to clean, durable and breathable, and is loved by consumers. However, the price of natural leather is relatively high and the resources are relatively scarce. Therefore, artificial leather has emerged as a substitute for natural leather. Compared with natural leather, artificial leather not only has the advantages of high utilization rate, strong wear resistance, easy cutting, but also alleviates the shortage of genuine leather resources in my country.
[0003] Artificial leather is a plastic product that looks and feels like leather and can be used instead of leather. It is usually made of fabric as the base, coated or calendered with synthetic resin and various plastic additives. According to the type of synthetic resin, it is divided into three categories: PVC artificial leather, PU artificial leather and SEBS artificial leather. PVC artificial leather requires a large amount of plasticizers during the processing, which is harmful to human health. In addition, PVC artificial leather becomes hard and brittle at low temperatures and cannot meet people's demand for high-end artificial leather. PU artificial leather has excellent wear resistance and low temperature resistance, but its hydrolysis resistance is poor, which seriously limits its scope of application. SEBS artificial leather is made of SEBS thermoplastic elastomer obtained by selective hydrogenation of the unsaturated double bonds of the butadiene segment in the block copolymer SBS molecule. It has good weather resistance, heat resistance, compression deformation resistance and low VOC release during the production process. In addition, SEBS artificial leather can be recycled and reused, and is expected to become an ideal alternative material for PVC and PU artificial leather.
[0004] With the popularity of SEBS artificial leather in the fields of home and automobile, the requirements for its flame retardant properties are getting higher and higher, but the current SEBS artificial leather cannot meet the requirements. In addition, in order to extend the service life of SEBS artificial leather, its tear resistance and wear resistance need to be improved urgently. Summary of the invention
[0005] In view of the defects of artificial leather in the prior art, one of the purposes of the present invention is to provide a tear-resistant, highly wear-resistant and highly flame-retardant SEBS elastomer material for artificial leather, which improves the tear resistance, wear resistance and flame retardancy while retaining the excellent properties of the SEBS elastomer itself.
[0006] The tear-resistant, highly wear-resistant and highly flame-retardant elastomeric material for artificial leather comprises the following components in parts by weight: 100 parts of SEBS; 1-5 parts of montmorillonite; 1-20 parts of phosphate flame retardant; 0.1-1.0 parts of crosslinking agent; 0.2-1.0 parts of accelerator; 1.0-5.0 parts of foaming agent; and 0.2-1.0 parts of antioxidant.
[0007] Optionally, the vinyl hydrogenation degree of the SEBS (hydrogenated styrene-butadiene block copolymer) is ≥97%; the montmorillonite includes at least one of organic montmorillonite and sodium montmorillonite; the phosphate flame retardant includes at least one of tricresyl phosphate, toluene xylene phosphate, trioctyl phosphate, triethyl phosphate, tripropyl phosphate, tributyl phosphate, tri(2-chloropropyl) phosphate, and tri(2-chloroethyl) phosphate; the crosslinking agent includes at least one of diisopropyl peroxide and di-tert-butyl diisopropyl peroxide; the foaming agent includes at least one of cyclopentyl peroxide and diisopropyl ditert-butyl peroxide; At least one of azodicarbonamide, a foaming agent H (N,N-dinitrosopentamethylenetetramine), a foaming agent ADC (azodicarbonamide), a foaming agent DNTA (N,N'-dinitrosopentamethylenetetramine), a foaming agent DAB (decanoylamidopropyl betaine), and a foaming agent AIBN (azobisisobutyronitrile); the accelerator is zinc oxide and / or zinc stearate; the antioxidant is composed of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and (2,4-di-tert-butylphenyl) triester in a mass ratio of 1:1.
[0008] The second object of the present invention is to provide a method for preparing the tear-resistant, highly wear-resistant and highly flame-retardant elastomeric artificial leather, which is simple to operate, low in cost and meets the requirements of industrial production. The preparation method is:
[0009] (1) At 25° C., montmorillonite and phosphate flame retardant are mixed in a certain mass ratio, stirred for a certain period of time using a dispersion sander, and then the mixture is placed in an oven for heating and vibrated and aged for a certain period of time using a vibrator, wherein the montmorillonite is peeled off into montmorillonite two-dimensional nanosheets, and the phosphate flame retardant finally obtained contains dispersed montmorillonite nanosheets;
[0010] (2) SEBS, accelerator, and antioxidant are weighed according to the mass ratio, mixed evenly, and pelletized in a twin-screw extruder at a certain temperature;
[0011] (3) adding the above-mentioned pellets, weighed cross-linking agent, foaming agent and the product of step (1) into an internal mixer and mixing them at a certain temperature for a certain time to obtain a mixed elastomeric material, and taking an appropriate amount to test the mechanical properties;
[0012] (4) adding the elastomeric material obtained in step (3) into a double-roll rubber mixer to form a sheet, and then sending it to a three-roll calender through a traction machine to be laminated with a base fabric. The laminated elastomeric base fabric is then sent to a foaming furnace through a traction machine to be micro-foamed at a certain temperature and time;
[0013] (5) Conducting performance tests on the artificial leather elastomer material after foaming.
[0014] Preferably, in the step (1), the mass ratio of montmorillonite to phosphate flame retardant is 1:(3-5), the stirring time of the dispersion sander is 3-5 min, the heating temperature of the oven is 50-70° C., the vibration frequency of the vibrator is 100-220 Hz, and the vibration aging time is 0.5-3 h; the granulation temperature in the step (2) is 185-200° C.; the banburying temperature in the step (3) is 145-160° C., and the banburying time is 3-5 min; the foaming temperature in the step (4) is 200-220° C., and the foaming time is 300-400 s;
[0015] More preferably, in the step (1), the mass ratio of montmorillonite to phosphate flame retardant is 1:4, the stirring time of the dispersion sander is 4 minutes, the heating temperature of the oven is 55° C., the vibration frequency of the vibrator is 160 Hz, and the vibration aging time is 1 hour; the granulation temperature in the step (2) is 190° C.; the banburying temperature in the step (3) is 150° C., and the banburying time is 4 minutes; the foaming temperature in the step (4) is 210° C., and the foaming time is 350 seconds;
[0016] The third object of the present invention is to provide an application of a tear-resistant, highly wear-resistant and highly flame-retardant elastomeric material for artificial leather, which can be applied to sofas, seats, leather goods, shoes and clothing, household goods, sports products, automobiles and other fields.
[0017] Beneficial effects:
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. At 25°C, montmorillonite and phosphate flame retardant are mixed in a certain mass ratio, stirred for a certain period of time using a dispersion sander, and then the mixture is placed in an oven for heating and vibrated by a vibrator for a certain period of time. This process peels off the montmorillonite into two-dimensional montmorillonite nanosheets, and the final phosphate flame retardant contains dispersed montmorillonite nanosheets. The specific mechanism is: the phosphate group easily forms hydrogen bond interactions with polar groups such as hydroxyl groups on the surface of montmorillonite, and is easily inserted into the interlayer of montmorillonite sheets, and with the help of an external vibrator, the nanosheets are peeled off. The reason for choosing organic montmorillonite and sodium montmorillonite is that these two types of montmorillonite have been treated in advance, and the interlayers have been relatively expanded. In addition, the vibration of phosphate ester and vibrator can accelerate the stripping efficiency of montmorillonite. The present invention obtains nano-montmorillonite with a thinner thickness by optimizing the preparation process of nano-montmorillonite, and introduces oven heating and vibrator vibration in the process to make the dispersion of montmorillonite in phosphate ester more uniform, so that the phosphate ester can be intercalated as soon as possible and promote its efficient stripping of montmorillonite. At the same time, a vibrator is installed to promote the stripping reaction, so that the stripping time of the entire nano-montmorillonite is greatly shortened, and the present invention is very suitable for large-scale industrial production.
[0020] 2. The nano-montmorillonite used in the present invention has a uniform morphology and an extremely low thickness. Therefore, when reinforcing SEBS, it has an extremely high dispersion and an effective interface in SEBS, and can have a high interface bonding strength with the SEBS matrix, thereby solving the current problems of insufficient dispersion of nano-level reinforcing materials in the reinforcing system and low interface bonding strength with the reinforcing system, and effectively improving the tear strength and wear resistance of the SEBS material. At the same time, the introduced phosphate ester can not only realize nano-level peeling of the montmorillonite, but also has the effect of a flame retardant. Adding this flame retardant has a certain optimization effect on the flame retardancy of the SEBS material.
[0021] 3. The preparation method of artificial leather proposed in the present invention is simple and easy to operate, has a high yield and low cost, and is suitable for large-scale industrial production. DETAILED DESCRIPTION
[0022] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.
[0023] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.
[0024] In this embodiment, the following performance tests are used:
[0025] Mechanical property test: According to the national standard GB / T 589-2008, the tear-resistant, wear-resistant and flame-retardant elastomer sample for artificial leather is a 120 mm × 6 mm × (2 ± 0.3) mm specimen.
[0026] Flammability test: GB / T 2407.
[0027] Tensile strength test: QJLY 7110614B-2015①5.5.
[0028] Peel strength: QJLY 7110614B-2015①5.9.
[0029] Folding fastness: QJLY7110614B-2015①5.11.
[0030] Cold resistance: QJLY7110614B-2015①5.15.
[0031] Heat aging resistance: QJLY7110614B-2015①5.13.
[0032] SEBS: Sinopec Baling Petrochemical Company, SEBS-604.
[0033] PVC: McLean, P815909.
[0034] Example 1
[0035] A tear-resistant, highly wear-resistant and highly flame-retardant elastomer material for artificial leather comprises the following components in parts by weight: 100 parts of SEBS, 3 parts of organic montmorillonite, 12 parts of tripropyl phosphate, 0.5 parts of dicumyl peroxide, 0.7 parts of zinc oxide, 2.5 parts of foaming agent ADC, 0.3 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.3 parts of (2,4-di-tert-butylphenyl) triester phosphite antioxidant.
[0036] The preparation steps of the elastomeric material include:
[0037] (1) At 25° C., 3 parts of organic montmorillonite and 12 parts of tripropyl phosphate were mixed in a mass ratio of 1:4, stirred for 4 min using a dispersion sander, and then the mixture was placed in an oven heated at 55° C. and equipped with a vibrator with a vibration frequency of 160 Hz for 1 h to obtain montmorillonite two-dimensional nanosheets;
[0038] (2) 100 parts of SEBS, 0.7 parts of zinc oxide, 0.3 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.3 parts of (2,4-di-tert-butylphenyl) triester phosphite antioxidant in a mass ratio of 1:1 were weighed, mixed evenly and pelletized in a twin-screw extruder at 190° C.;
[0039] (3) adding the above pellets, 0.5 parts of dicumyl peroxide, 2.5 parts of foaming agent ADC and the product of step (1) into an internal mixer and mixing at 150° C. for 4 min to obtain an internally mixed elastomeric material, and taking an appropriate amount to test the mechanical properties;
[0040] (4) adding the elastomeric material obtained in step (3) into a double-roll rubber mixer to form a sheet, and then sending it to a three-roll calender through a traction machine to be laminated with a base fabric. The laminated elastomeric base fabric is sent to a foaming furnace through a traction machine to be micro-foamed at 210° C. for 350 seconds;
[0041] (5) Conducting performance tests on the artificial leather elastomer material after foaming.
[0042] The experimental results are shown in Tables 1 and 2.
[0043] Example 2
[0044] A tear-resistant, highly wear-resistant and highly flame-retardant elastomer material for artificial leather comprises the following components in parts by weight: 100 parts of SEBS, 3 parts of sodium montmorillonite, 12 parts of tripropyl phosphate, 0.5 parts of dicumyl peroxide, 0.7 parts of zinc oxide, 2.5 parts of foaming agent ADC, 0.3 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.3 parts of (2,4-di-tert-butylphenyl) triester phosphite antioxidant.
[0045] The preparation steps of the elastomeric material include:
[0046] (1) At 25° C., 3 parts of sodium montmorillonite and 12 parts of tripropyl phosphate were mixed in a mass ratio of 1:4, stirred for 4 min using a dispersion sander, and then the mixture was placed in an oven heated at 55° C. and a vibrator was installed at a vibration frequency of 160 Hz for 1 h to obtain montmorillonite two-dimensional nanosheets;
[0047] (2) 100 parts of SEBS, 0.7 parts of zinc oxide, 0.3 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.3 parts of (2,4-di-tert-butylphenyl) triester phosphite antioxidant in a mass ratio of 1:1 were weighed, mixed evenly and pelletized in a twin-screw extruder at 190° C.;
[0048] (3) adding the above pellets, 0.5 parts of dicumyl peroxide, 2.5 parts of foaming agent ADC and the product of step (1) into an internal mixer and mixing at 150° C. for 4 min to obtain an internally mixed elastomeric material, and taking an appropriate amount to test the mechanical properties;
[0049] (4) adding the elastomeric material obtained in step (3) into a double-roll rubber mixer to form a sheet, and then sending it to a three-roll calender through a traction machine to be laminated with a base fabric. The laminated elastomeric base fabric is sent to a foaming furnace through a traction machine to be micro-foamed at 210° C. for 350 seconds;
[0050] (5) Conducting performance tests on the artificial leather elastomer material after foaming.
[0051] The experimental results are shown in Tables 1 and 2.
[0052] Example 3
[0053] A tear-resistant, highly wear-resistant and highly flame-retardant elastomer material for artificial leather comprises the following components in parts by weight: 100 parts of SEBS, 3 parts of organic montmorillonite, 12 parts of tris(2-chloropropyl) phosphate, 0.5 parts of dicumyl peroxide, 0.7 parts of zinc oxide, 2.5 parts of foaming agent ADC, 0.3 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.3 parts of (2,4-di-tert-butylphenyl) triester phosphite antioxidant.
[0054] The preparation steps of the elastomeric material include:
[0055] (1) At 25° C., 3 parts of organic montmorillonite and 12 parts of tris(2-chloropropyl) phosphate were mixed in a mass ratio of 1:4, stirred for 4 min using a dispersion sander, and then the mixture was placed in an oven heated at 55° C. and equipped with a vibrator with a vibration frequency of 160 Hz for 1 h to obtain montmorillonite two-dimensional nanosheets;
[0056] (2) 100 parts of SEBS, 0.7 parts of zinc oxide, 0.3 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.3 parts of (2,4-di-tert-butylphenyl) triester phosphite antioxidant in a mass ratio of 1:1 were weighed, mixed evenly and pelletized in a twin-screw extruder at 190° C.;
[0057] (3) adding the above pellets, 0.5 parts of dicumyl peroxide, 2.5 parts of foaming agent ADC and the product of step (1) into an internal mixer and mixing at 150° C. for 4 min to obtain an internally mixed elastomeric material, and taking an appropriate amount to test the mechanical properties;
[0058] (4) adding the elastomeric material obtained in step (3) into a double-roll rubber mixer to form a sheet, and then sending it to a three-roll calender through a traction machine to be laminated with a base fabric. The laminated elastomeric base fabric is sent to a foaming furnace through a traction machine to be micro-foamed at 210° C. for 350 seconds;
[0059] (5) Conducting performance tests on the artificial leather elastomer material after foaming.
[0060] The experimental results are shown in Tables 1 and 2.
[0061] Example 4
[0062] A tear-resistant, highly wear-resistant and highly flame-retardant elastomer material for artificial leather comprises the following components in parts by weight: 100 parts of SEBS, 3 parts of organic montmorillonite, 9 parts of tripropyl phosphate, 0.5 parts of dicumyl peroxide, 0.7 parts of zinc oxide, 2.5 parts of foaming agent ADC, 0.3 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.3 parts of (2,4-di-tert-butylphenyl) triester phosphite antioxidant.
[0063] The preparation steps of the elastomeric material include:
[0064] (1) At 25° C., 3 parts of organic montmorillonite and 9 parts of tripropyl phosphate were mixed in a mass ratio of 1:3, stirred for 4 min using a dispersion sander, and then the mixture was placed in an oven heated at 55° C. and equipped with a vibrator with a vibration frequency of 160 Hz for 1 h to obtain montmorillonite two-dimensional nanosheets;
[0065] (2) 100 parts of SEBS, 0.7 parts of zinc oxide, 0.3 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.3 parts of (2,4-di-tert-butylphenyl) triester phosphite antioxidant in a mass ratio of 1:1 were weighed, mixed evenly and pelletized in a twin-screw extruder at 190° C.;
[0066] (3) adding the above pellets, 0.5 parts of dicumyl peroxide, 2.5 parts of ADC and the product of step (1) into an internal mixer and mixing at 150° C. for 4 min to obtain an internally mixed elastomeric material, and taking an appropriate amount to test the mechanical properties;
[0067] (4) adding the elastomeric material obtained in step (3) into a double-roll rubber mixer to form a sheet, and then sending it to a three-roll calender through a traction machine to be laminated with a base fabric. The laminated elastomeric base fabric is sent to a foaming furnace through a traction machine to be micro-foamed at 210° C. for 350 seconds;
[0068] (5) Conducting performance tests on the artificial leather elastomer material after foaming.
[0069] The experimental results are shown in Tables 1 and 2.
[0070] Example 5
[0071] A tear-resistant, highly wear-resistant and highly flame-retardant elastomer material for artificial leather comprises the following components in parts by weight: 100 parts of SEBS, 3 parts of organic montmorillonite, 15 parts of tripropyl phosphate, 0.5 parts of dicumyl peroxide, 0.7 parts of zinc oxide, 2.5 parts of foaming agent ADC, 0.3 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.3 parts of (2,4-di-tert-butylphenyl) triester phosphite antioxidant.
[0072] The preparation steps of the elastomeric material include:
[0073] (1) At 25° C., 3 parts of organic montmorillonite and 15 parts of tripropyl phosphate were mixed in a mass ratio of 1:5, and stirred for 4 minutes using a dispersion sander. The mixture was then placed in an oven heated at 55° C. and equipped with a vibrator with a vibration frequency of 160 Hz for 1 hour to obtain montmorillonite two-dimensional nanosheets;
[0074] (2) 100 parts of SEBS, 0.7 parts of zinc oxide, 0.3 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.3 parts of (2,4-di-tert-butylphenyl) triester phosphite antioxidant in a mass ratio of 1:1 were weighed, mixed evenly and pelletized in a twin-screw extruder at 190° C.;
[0075] (3) adding the above pellets, 0.5 parts of dicumyl peroxide, 2.5 parts of ADC and the product of step (1) into an internal mixer and mixing at 150° C. for 4 min to obtain an internally mixed elastomeric material, and taking an appropriate amount to test the mechanical properties;
[0076] (4) adding the elastomeric material obtained in step (3) into a double-roll rubber mixer to form a sheet, and then sending it to a three-roll calender through a traction machine to be laminated with a base fabric. The laminated elastomeric base fabric is sent to a foaming furnace through a traction machine to be micro-foamed at 210° C. for 350 seconds;
[0077] (5) Conducting performance tests on the artificial leather elastomer material after foaming.
[0078] The experimental results are shown in Tables 1 and 2.
[0079] Example 6
[0080] A tear-resistant, highly wear-resistant and highly flame-retardant elastomer material for artificial leather comprises the following components in parts by weight: 100 parts of SEBS, 1 part of organic montmorillonite, 1 part of tripropyl phosphate, 0.1 part of dicumyl peroxide, 0.2 part of zinc oxide, 1 part of foaming agent ADC, 0.1 part of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and 0.1 part of (2,4-di-tert-butylphenyl) triester phosphite antioxidant.
[0081] The preparation steps of the elastomeric material include:
[0082] (1) At 25° C., 1 part of organic montmorillonite and 1 part of tripropyl phosphate were mixed in a mass ratio of 1:1, stirred for 4 min using a dispersion sander, and then the mixture was placed in an oven heated at 55° C. and equipped with a vibrator with a vibration frequency of 160 Hz for 1 h to obtain montmorillonite two-dimensional nanosheets;
[0083] (2) 100 parts of SEBS, 0.2 parts of zinc oxide, 0.1 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.1 parts of (2,4-di-tert-butylphenyl) triester phosphite antioxidant in a mass ratio of 1:1 were weighed, mixed evenly and pelletized in a twin-screw extruder at 190° C.;
[0084] (3) adding the above pellets, 0.1 parts of dicumyl peroxide, 1 part of ADC and the product of step (1) into an internal mixer and mixing at 150° C. for 4 min to obtain an internally mixed elastomeric material, and taking an appropriate amount to test the mechanical properties;
[0085] (4) adding the elastomeric material obtained in step (3) into a double-roll rubber mixer to form a sheet, and then sending it to a three-roll calender through a traction machine to be laminated with a base fabric. The laminated elastomeric base fabric is sent to a foaming furnace through a traction machine to be micro-foamed at 210° C. for 350 seconds;
[0086] (5) Conducting performance tests on the artificial leather elastomer material after foaming.
[0087] The formula composition and experimental results are shown in Table 1 and Table 2.
[0088] Example 7 (The difference between this example and Example 1 is that the number of added portions of all formulas is the highest, and the other conditions are the same as those of Example 1.)
[0089] A tear-resistant, highly wear-resistant and highly flame-retardant elastomer material for artificial leather comprises the following components in parts by weight: 100 parts of SEBS, 5 parts of organic montmorillonite, 20 parts of tripropyl phosphate, 1 part of dicumyl peroxide, 1 part of zinc oxide, 5 parts of foaming agent ADC, 0.5 part of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.5 part of (2,4-di-tert-butylphenyl) triester phosphite antioxidant.
[0090] The preparation steps of the elastomeric material include:
[0091] (1) At 25° C., 5 parts of organic montmorillonite and 20 parts of tripropyl phosphate were mixed in a mass ratio of 1:4, stirred for 4 min using a dispersion sander, and then the mixture was placed in an oven heated at 55° C. and equipped with a vibrator with a vibration frequency of 160 Hz for 1 h to obtain montmorillonite two-dimensional nanosheets;
[0092] (2) 100 parts of SEBS, 1 part of zinc oxide, 0.5 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.5 parts of (2,4-di-tert-butylphenyl) triester phosphite antioxidant in a mass ratio of 1:1 were weighed, mixed evenly and pelletized in a twin-screw extruder at 190° C.;
[0093] (3) adding the above pellets, 1 part of dicumyl peroxide, 5 parts of ADC and the product of step (1) into an internal mixer and mixing at 150° C. for 4 min to obtain an internally mixed elastomeric material, and taking an appropriate amount to test the mechanical properties;
[0094] (4) adding the elastomeric material obtained in step (3) into a double-roll rubber mixer to form a sheet, and then sending it to a three-roll calender through a traction machine to be laminated with a base fabric. The laminated elastomeric base fabric is sent to a foaming furnace through a traction machine to be micro-foamed at 210° C. for 350 seconds;
[0095] (5) Conducting performance tests on the artificial leather elastomer material after foaming.
[0096] The experimental results are shown in Tables 1 and 2.
[0097] Example 8
[0098] A tear-resistant, highly wear-resistant and highly flame-retardant elastomer material for artificial leather comprises the following components in parts by weight: 100 parts of SEBS, 3 parts of organic montmorillonite, 12 parts of tripropyl phosphate, 0.5 parts of dicumyl peroxide, 0.7 parts of zinc oxide, 2.5 parts of foaming agent ADC, 0.3 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.3 parts of (2,4-di-tert-butylphenyl) triester phosphite antioxidant.
[0099] The preparation steps of the elastomeric material include:
[0100] (1) At 25° C., 3 parts of organic montmorillonite and 12 parts of tripropyl phosphate were mixed in a mass ratio of 1:4, and stirred for 3 minutes using a dispersion sander. The mixture was then placed in an oven heated at 50° C. and equipped with a vibrator with a vibration frequency of 100 Hz for 0.5 hours to obtain montmorillonite two-dimensional nanosheets;
[0101] (2) 100 parts of SEBS, 0.7 parts of zinc oxide, 0.3 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.3 parts of (2,4-di-tert-butylphenyl) triester phosphite antioxidant in a mass ratio of 1:1 were weighed, mixed evenly and pelletized in a twin-screw extruder at 185° C.;
[0102] (3) adding the above pellets, 0.5 parts of dicumyl peroxide, 2.5 parts of ADC and the product of step (1) into an internal mixer and mixing at 145° C. for 5 min to obtain an elastomeric material after mixing, and taking an appropriate amount to test the mechanical properties;
[0103] (4) adding the elastomeric material obtained in step (3) into a double-roll rubber mixer to form a sheet, and then sending it to a three-roll calender through a traction machine to be laminated with a base fabric. The laminated elastomeric base fabric is sent to a foaming furnace through a traction machine to be micro-foamed at 200° C. for 300 seconds;
[0104] (5) Conducting performance tests on the artificial leather elastomer material after foaming.
[0105] The experimental results are shown in Tables 1 and 2.
[0106] Example 9
[0107] A tear-resistant, highly wear-resistant and highly flame-retardant elastomer material for artificial leather comprises the following components in parts by weight: 100 parts of SEBS, 3 parts of organic montmorillonite, 12 parts of tripropyl phosphate, 0.5 parts of dicumyl peroxide, 0.7 parts of zinc oxide, 2.5 parts of foaming agent ADC, 0.3 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.3 parts of (2,4-di-tert-butylphenyl) triester phosphite antioxidant.
[0108] The preparation steps of the elastomeric material include:
[0109] (1) At 25° C., 3 parts of organic montmorillonite and 12 parts of tripropyl phosphate were mixed in a mass ratio of 1:4, stirred for 5 minutes using a dispersion sander, and then the mixture was placed in an oven heated at 70° C. and equipped with a vibrator with a vibration frequency of 220 Hz for aging for 3 hours to obtain montmorillonite two-dimensional nanosheets;
[0110] (2) 100 parts of SEBS, 0.7 parts of zinc oxide, 0.3 parts of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and 0.3 parts of (2,4-di-tert-butylphenyl) triester phosphite antioxidant in a mass ratio of 1:1 were weighed, mixed evenly and pelletized in a twin-screw extruder at 200° C.;
[0111] (3) adding the above pellets, 0.5 parts of dicumyl peroxide, 2.5 parts of ADC and the product of step (1) into an internal mixer and mixing at 160° C. for 5 min to obtain an elastomeric material after mixing, and taking an appropriate amount to test the mechanical properties;
[0112] (4) adding the elastomeric material obtained in step (3) into a double-roll rubber mixer to form a sheet, and then sending it to a three-roll calender through a traction machine to be laminated with a base fabric. The laminated elastomeric base fabric is sent to a foaming furnace through a traction machine to be micro-foamed at 220° C. for 400 seconds;
[0113] (5) Conducting performance tests on the artificial leather elastomer material after foaming.
[0114] The experimental results are shown in Tables 1 and 2.
[0115] Comparative Example 1
[0116] The difference between Comparative Example 1 and Example 1 is that montmorillonite is directly used to reinforce SEBS, step 1 is omitted, and the other conditions are the same as those of Example 1. The test results are shown in Table 1.
[0117] Comparative Example 2
[0118] The difference between Comparative Example 2 and Example 1 is that the mass ratio of montmorillonite to phosphate flame retardant is 1:5, and the other conditions are the same as those of Example 1. The test results are shown in Table 1.
[0119] Comparative Example 3
[0120] The difference between Comparative Example 3 and Example 1 is that the mass ratio of montmorillonite to phosphate flame retardant is 1:2, and the other conditions are the same as those of Example 1. The test results are shown in Table 1.
[0121] Comparative Example 4
[0122] The difference between Comparative Example 4 and Example 1 is that the flame retardant is replaced with antimony trioxide, and the other conditions are the same as those of Example 1. The test results are shown in Table 1.
[0123] Comparative Example 5
[0124] Step (1) was heated in a common oven at 55° C. without a vibrator. Other conditions were the same as those in Example 1. The test results are shown in Table 1.
[0125] Comparative Example 6
[0126] SEBS was replaced with PVC of the same mass fraction, and other conditions were the same as those in Example 1. The test results are shown in Table 1.
[0127] Table 1: Mechanical property test results of the elastomeric materials obtained in Examples 1-9 and Comparative Examples 1-6 (products of step 3)
[0128]
[0129] Table 2: Performance test results of artificial leather materials (products of step 5) obtained in Examples 1-9 and Comparative Examples 1-6
[0130]
[0131]
[0132]
[0133] According to the experimental results, the introduction of nano-montmorillonite can effectively enhance SEBS because nano-montmorillonite has a very high specific surface area. Therefore, when enhancing SEBS, it can have a higher dispersion and interaction area in SEBS, and can also have a higher interface bonding strength with the SEBS matrix, effectively solving the current dispersion and interface bonding problems faced by nano-level material enhancement, thereby improving the tear strength and wear resistance of SEBS materials. The introduced phosphate ester can not only achieve nano-level stripping of montmorillonite, but also has the function of a flame retardant, which can optimize the flame retardancy of SEBS materials to a certain extent. The phosphate flame retardant introduced in the embodiment has a strong interaction and stripping effect with montmorillonite. When heated in an oven and a vibrator is introduced, the stripping speed can be effectively accelerated, and the montmorillonite structure will not be damaged at a specific time and vibration frequency. However, according to the comparative experimental results, when the phosphate flame retardant is not added or the flame retardant is changed, the reinforcement effect of SEBS is significantly reduced. The reinforcement of the material is related to the dispersion of the enhanced montmorillonite and the interfacial bonding strength with SEBS. The lower the thickness of the montmorillonite, the higher these two values are, which indirectly indicates that changing the stripping reaction conditions will affect the stripping of the montmorillonite, thereby failing to obtain a nano-scale montmorillonite with uniform distribution and lower thickness.
[0134] According to Examples 1-2, tripropyl phosphate can achieve the stripping of organic montmorillonite and sodium montmorillonite, but the stripping effect of organic montmorillonite is better, because the sodium ions at the end of sodium montmorillonite will increase the difficulty of stripping, thereby reducing the stripping efficiency, so both nano-montmorillonite have a good reinforcing effect on SEBS elastomer materials, but the nano-organic montmorillonite has a better relative reinforcing effect, and the artificial leather obtained by the elastomer has excellent flame retardancy, tensile strength, peel strength, fatigue resistance, weather resistance and low VOC emission. The type of phosphate flame retardant will also affect the stripping of montmorillonite and the enhancement of SEBS. When replaced with tris (2-chloropropyl) phosphate with halogen elements, although the enhanced SEBS obtained has good mechanical properties and performance, the chlorine atoms contained at the end of this type of phosphate flame retardant will increase the release of VOC. This can be verified from the experimental results of Examples 1 and 3. As tripropyl phosphate was replaced with tri(2-chloropropyl) phosphate, VOC increased significantly, but other properties of SEBS did not differ significantly.
[0135] The mass ratio of montmorillonite and phosphate ester will also affect the stripping of montmorillonite. According to the experimental results of Examples 4-5 and Comparative Examples 2-3, when the mass ratio of montmorillonite and phosphate ester is relatively low, the phosphate ester has a higher concentration, and the difficulty of montmorillonite stripping is reduced. However, when the output of nano-layered montmorillonite reaches a certain level, it will affect the movement of ordinary montmorillonite molecular chains, the system viscosity is low, and the amount of nano-layered montmorillonite obtained is reduced, which is not conducive to the subsequent enhancement of SEBS; when the concentration of phosphate ester is low, the difficulty of montmorillonite stripping increases, because the excessive amount of montmorillonite added makes the viscosity of the entire system larger, resulting in a smaller amount of nano-layered montmorillonite obtained, which affects the enhancement of SEBS.
[0136] According to Examples 6-9, when the ingredient ratio is constant, too low or too high process parameters will affect the stripping of montmorillonite and the subsequent enhancement of montmorillonite, resulting in an unclear enhancement effect of SEBS. Therefore, when the ingredient ratio is constant, appropriate process parameters are required to achieve a better montmorillonite stripping effect, thereby effectively enhancing SEBS.
[0137] According to Comparative Example 6, although nano-montmorillonite can have a certain strengthening effect on PVC, its low-temperature resistance still has a large defect, which is not conducive to its use at low temperatures.
Claims
1. A tear-resistant, wear-resistant and flame-retardant elastomeric material for artificial leather, characterized in that: The elastomer material comprises the following components in parts by weight: 100 parts of SEBS; 1-5 parts of montmorillonite; 1-20 parts of phosphate flame retardant; 0.1-1.0 parts of crosslinking agent; 0.2-1.0 parts of accelerator; 1.0-5.0 parts of foaming agent; and 0.2-1.0 parts of antioxidant.
2. The tear-resistant, wear-resistant and flame-retardant elastomer material for artificial leather according to claim 1, characterized in that: The vinyl hydrogenation degree of the SEBS is ≥97%.
3. The tear-resistant, wear-resistant and flame-retardant elastomer material for artificial leather according to claim 1, characterized in that: The montmorillonite includes at least one of organic montmorillonite and sodium-based montmorillonite.
4. The tear-resistant, wear-resistant and flame-retardant elastomer material for artificial leather according to claim 1, characterized in that: The phosphate flame retardant includes at least one of tricresyl phosphate, cresyl xylene phosphate, trioctyl phosphate, triisopropyl phosphate, tripropyl phosphate, tributyl phosphate, tri(2-chloropropyl) phosphate, and tri(2-chloroethyl) phosphate.
5. The tear-resistant, wear-resistant and flame-retardant elastomer material for artificial leather according to claim 1, characterized in that: The cross-linking agent includes at least one of dicumyl peroxide and di-tert-butyl dicumyl peroxide.
6. The tear-resistant, wear-resistant and flame-retardant elastomer material for artificial leather according to claim 1, characterized in that: The foaming agent includes at least one of azodicarbonamide, foaming agent H, foaming agent ADC, foaming agent DNTA, foaming agent DAB, and foaming agent AIBN; the accelerator includes zinc oxide and / or zinc stearate; and the antioxidant is composed of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and (2,4-di-tert-butylphenyl) triester in a mass ratio of 1:
1.
7. A method for preparing the tear-resistant, wear-resistant and flame-retardant elastomer material for artificial leather as claimed in claim 1, characterized in that: The specific preparation steps are: (1) at 25° C., montmorillonite and a phosphate flame retardant were mixed according to a mass ratio, stirred using a dispersion sander, and then the mixture was placed in an oven for heating and vibrated by a vibrator to obtain a phosphate flame retardant dispersed with montmorillonite nanosheets; (2) SEBS, accelerator, and antioxidant are weighed according to the mass ratio, mixed evenly, and then transferred to a twin-screw extruder for granulation; (3) adding the above-mentioned pellets, weighed cross-linking agent, foaming agent and the product of step (1) into an internal mixer for internal mixing to obtain an internally mixed elastomeric material; (4) adding the elastomeric material obtained in step (3) into a double-roll rubber mixer to form a sheet, and then sending it to a three-roll calender through a traction machine to be laminated with a base fabric, and the laminated elastomeric base fabric is sent to a foaming furnace through a traction machine for micro-foaming; (5) Conducting performance tests on the artificial leather elastomer material after foaming.
8. The method for preparing the tear-resistant, highly wear-resistant and highly flame-retardant elastomer material for artificial leather according to claim 7, characterized in that: In the step (1), the mass ratio of montmorillonite to phosphate flame retardant is 1:(3-5), the stirring time of the dispersion sander is 3-5 minutes, the heating temperature of the oven is 50-70°C, the vibration frequency of the vibrator is 100-220Hz, and the vibration aging time is 0.5-3h; the granulation temperature in the step (2) is 185-200°C; the banburying temperature in the step (3) is 145-160°C, and the banburying time is 3-5 minutes; the foaming temperature in the step (4) is 200-220°C, and the foaming time is 300-400s.
9. The method for preparing the tear-resistant, highly wear-resistant and highly flame-retardant elastomer material for artificial leather according to claim 8, characterized in that: In the step (1), the mass ratio of montmorillonite to phosphate flame retardant is 1:4, the stirring time of the dispersion sander is 4 minutes, the heating temperature of the oven is 55° C., the vibration frequency of the vibrator is 160 Hz, and the vibration aging time is 1 hour; the granulation temperature in the step (2) is 190° C.; the banburying temperature in the step (3) is 150° C., and the banburying time is 4 minutes; and the foaming temperature in the step (4) is 210° C., and the foaming time is 350 seconds.
10. An application of the tear-resistant, wear-resistant and flame-retardant elastomer material for artificial leather according to any one of claims 1 to 6, characterized in that: The tear-resistant, highly wear-resistant and highly flame-retardant elastomer material for artificial leather is applied to sofas, seats, leather goods, shoes and clothing, household goods, sports products and automobile fields.
Citation Information
Cited By
High-weather-resistance fluorocarbon powder coating as well as preparation method and application thereof
CN120758144A